Nusantara: A Study of Maritime Geopolitics and National Identity of Indonesia's Future Capital City - Imawan, Riswanda; Reynaldi, Hendy Achmad (CV. Strata Persada Academia, 2025)
This research aims to examine the impact of moving the capital city on Indonesia's geopolitical dynamics and how this move contributes to the transformation of national identity. Rimland Theory is used to analyze the geopolitical aspects, highlighting the importance of the Nusantara's position at the center of the Asia-Pacific region and its potential impact on Indonesia's influence in the region. Benedict Anderson's Imagined Communities provides a framework for understanding how the relocation of the capital city could redefine Indonesia's national identity, by introducing an inclusive narrative that transcends the dominance of Javanese culture. This research uses a qualitative approach with document analysis and interviews with political, social and cultural experts. The findings show that relocating the capital city has the potential to accelerate equitable development and strengthen Indonesia's position in the international arena. In addition, the relocation of the capital city also opens up opportunities to create a more inclusive national narrative, by recognizing cultural diversity outside Java. The novelty of this research lies in the application of both theories to examine the role of the archipelago as a new symbol that represents transformation in the geopolitical aspects and national identity of Indonesia.